Identification of nucleoid associated proteins (NAPs) under oxidative stress in Staphylococcus aureus - 大庭 良介; 森川 一也; Ushijima Yuri; Ohniwa Ryosuke L.; Morikawa Kazuya (BMC microbiology, 2017)
Background\nBacterial nucleoid consists of genome DNA, RNA, and hundreds of nucleoid-associated proteins (NAPs). Escherichia coli nucleoid is compacted towards the stationary phase, replacing most log-phase NAPs with the major stationary-phase nucleoid protein, Dps. In contrast, Staphylococcus aureus nucleoid sustains the fiber structures throughout the growth. Instead, the Dps homologue, MrgA, expresses under oxidative stress conditions to clump the nucleoid, but the composition of the clumped nucleoid was elusive.\nResults\nThe staphylococcal nucleoid under oxidative stress was isolated by sucrose gradient centrifugation, and the proteins were analyzed by liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). We identified 299 proteins in the nucleoid under oxidative stress, including 113 csNAPs (contaminant-subtracted NAPs). Comparison with the previously identified csNAPs in log- and stationary phase indicated that one fifth of the csNAPs under oxidative stress were the constitutive nucleoid components; importantly, several factors including HU, SarA, FabZ, and ribosomes were sustained under oxidative stress. Some factors (e.g. SA1663 and SA0092/SA0093) with unknown functions were included in the csNAPs list specifically under oxidative stress condition.\nConclusion\nNucleoid constitutively holds Hu, SarA, FabG, and ribosomal proteins even under the oxidative stress, reflecting the active functions of the clumped nucleoid, unlikely to the dormant E. coli nucleoid compacted in the stationary phase or starvation.